DDB2 gene disruption leads to skin tumors and resistance to apoptosis after exposure to ultraviolet light but not a chemical carcinogen - Itoh, Toshiki (National Academy of Sciences, 2004)
Mutations in the human DDB2 gene give rise to xeroderma pigmentosum group E, a disease characterized by increased skin tumorigenesis in response to UV-irradiation. Cell strains derived from xeroderma pigmentosum group E individuals also have enhanced resistance to UV-irradiation due to decreased p53-mediated apoptosis. To further address the precise function(s) of DDB2 and the consequence of non-naturally occurring DDB2 mutations, we generated mice with a disruption of the gene. The mice exhibited significantly enhanced skin carcinogenesis in response to UV-irradiation, and cells from the DDB2(–/–) mice were abnormally resistant to killing by the radiation and had diminished UV-induced, p53-mediated apoptosis. Notably, the cancer-prone phenotype and the resistance to cellular killing were not observed after exposure to the chemical carcinogen, 7,12-dimethylbenz[a]anthracene (DMBA), to which mice carrying defective nucleotide excision repair genes respond with enhanced tumors and cell killing. Although cells from heterozygous DDB2(+/–) mice appeared normal, these mice had enhanced skin carcinogenesis after UV-irradiation, so that XP-E heterozygotes might be at risk for carcinogenesis. In sum, these results demonstrate that DDB2 is well conserved between humans and mice and functions as a tumor suppressor, at least in part, by controlling p53-mediated apoptosis after UV-irradiation.